Improvement the Quality of Fish Oil from Waste Flouring Using Adsorbent Zeolit H5-NZA - Donatus Setyawan Purwo Handoko; R. Yuni Ristanti; Wuryanti Handayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Flouring process produces fish oil fractions colored dark brown and has a free fatty acid levels are high. This causes the oil fraction can be easily damaged and rancid. This problem can be overcome by purification by means of degumming first and then the fish oil the gross adsorbed using adsorbents natural zeolite (NZ) and H5-NZA with the composition of the adsorbent 10%, 15%, 20%, and 25% (w / w fish oil ) on the adsorption process temperature of 50 ° C, 70 ° C, 90 ° C. Adsorbent characterization results indicate that an increase in acidity and Si / Al ratio of zeolites that have been activated are H5-NZA. Increased acidity of 0.291 mmol / gram to 3,570 mmol / gram, while increasing the ratio of Si / Al of 4.373 into 6.398. The quality of fish oil before and after the adsorbed adsorbed using adsorbents also increased. H5-NZA adsorbent provides enhanced quality greater than the natural zeolite adsorbent. Improved quality is shown with increasing adsorbent composition. Adsorbent composition that provides improved quality of most good is a composition of 25%, while the adsorption process temperature optimum at 70 ° C